Grip strength, body composition, and mortality. - Gale, C; Martyn, C; Cooper, C; Sayer, A (2007)
BACKGROUND: Several studies in older people have shown that grip strength predicts all-cause mortality. The mechanisms are unclear. Muscle strength declines with age, accompanied by a loss of muscle mass and an increase in fat, but the role that body composition plays in the association between grip strength and mortality has been little explored. We investigated the relation between grip strength, body composition, and cause-specific and total mortality in 800 men and women aged 65 and over. METHODS: During 197374 the UK Department of Health and Social Security surveyed random samples of men and women aged 65 and over living in eight areas of Britain to assess the nutritional state of the elderly population. The survey included a clinical examination by a geriatrician who assessed grip strength and anthropometry. We used Cox proportional hazards models to examine mortality over 24 years of follow-up. RESULTS: Poorer grip strength was associated with increased mortality from all-causes, from cardiovascular disease, and from cancer in men, though not in women. After adjustment for potential confounding factors, including arm muscle area and BMI, the relative risk of death in men was 0.81 (95% CI 0.700.95) from all-causes, 0.73 (95% CI 0.600.89) from cardiovascular disease, and 0.81 (95% CI 0.660.98) from cancer per SD increase in grip strength. These associations remained statistically significant after further adjustment for fat-free mass or % body fat. CONCLUSION: Grip strength is a long-term predictor of mortality from all-causes, cardiovascular disease, and cancer in men. Muscle size and other indicators of body composition did not explain these associations.